An investigation on design innovation, fabrication and experiment of a soy bean peeling machine-scale - Nguyen, Van Thanh Tien; Anh Dang, Van; Thoai Tran, Ngoc; Hoang Nguyen, Cong; Hoa Vo, Dai; Khoa Nguyen, Dang; Lam Nguyen, Ngoc; Lam Nguyen, Quang; Long Tieu, Thien; Nam Bui, Tan; Bao Tran, Tien (International Journal of Engineering and Technology, 2018)
This study on the mentioned machine is to intend to peel seed coat of dried soybean that applies the friction principles between the seed coat and the conveyor belt. Creating largely frictional contact on the surface of the soybeans leads to the broken link of the seed coat which is responsible for peeling away the seed coat from the soybeans completely. This work demonstrates the design parameters and the fabrication method including the number of rotations of the two conveyors, the contact distance between the conveyor and soybeans. The recommended values of the parameters after studying are carried out as following: the revolution is 120 rpm, the gap between the conveyor and the bean is 6 mm and the conveyor belt width is 400 mm. Based on these results, the finished product reaches around 80.06 percent and the productivity achieves 15 kilograms per hour. Â